Evaluation of split-radix IFFT algorithms in hardware (MASKAY, 2018)
The present work focuses on a hardware-based approach to experimentally identify the best-performing algorithm for calculating the IFFT of an OFDM symbol of the ISDBT-b standard. To accomplish this goal, symmetric and asymmetric Split-radix algorithms are described, and their entire hardware implementation is developed. The test results incorporate other algorithms known as radix-2 lite, radix-2, radix-4, and pipelined.  The comparative evaluation of the performance of the algorithms was performed considering the following parameters: Signal to Quantize Noise Ratio (SQNR), processing time, and the amount of resources used by the Virtex-5 XUPV5-LX110T card. The analysis shows that the algorithm that presents the best performance depends on the parameter analyzed.
Keywords: IFFT; Splir-radix; IFFT algoritms